PERCEIVED ORGANIZATIONAL SUPPORT, ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION: EFFECTS ON SICKNESS ABSENTEEISM IN THE LOCAL PUBLIC SECTOR - Fatéma SAFY-GODINEAU; Amar FALL; David CARASSUS (Revue de Gestion des Ressources Humaines, 2020)
Our study examines the respective influence of perceived organizational support, the three components of organizational commitment, and work satisfaction on local public organization employees’ sickness absenteeism. The research results, based on a sample of 942 local public organization employees, show the conditions under which their sickness absenteeism is more likely to occur. Thus, a low perception of organizational support, a high calculated organizational commitment, as well as an affective organizational commitment combined with low work satisfaction, are identified as potential determinants of sickness absenteeism. Our research suggests that local public organization employees’ sickness absenteeism is the consequence of their organizational disenchantment and their opportunistic attitude. Moreover, our research emphasizes the importance of organizational support as a potential motivator to reduce sickness absenteeism. The research’s main contributions draw the attention of local public managers on the necessity of a supportive workplace that promotes affective organizational commitment and work satisfaction to reduce sickness related absenteeism.